A comparative safety study of the mother-and-child technique with the same size radial sheath and the same size guide for transradial percutaneous coronary intervention - Satish Rameshrao Chirde; Narendra R. Bachewar; Amar S. Wani; Neha S. Chirde (Heart India)
Background: Transradial access (TRA) has reduced vascular complications, but still certain complications are experienced. We studied the mother-and-child technique for TRA, which hoped to reduce further certain TRA complications. Aims: This research sought to evaluate complications associated with TRA between two groups: one utilizing a 7F sheath with a 6F percutaneous transluminal coronary angioplasty (PTCA) catheter and another using a 6F sheath with a 6F PTCA catheter. Settings and Design: A nonrandomized, single-institution observational study was conducted over a 12-month period. Subjects and Methods: One hundred and thirty-two subjects undergoing transradial PTCA were divided into two groups: one employed a 7F radial Cordis sheath with a 6F PTCA catheter (mother-and-child technique), whereas another used a 6F Cordis radial sheath with a 6F PTCA catheter. We excluded hemodynamically unstable patients, who required emergency treatment, or had a negative Allen’s test. Statistical Analysis Used: Means and standard deviations were utilized to report continuous variables, whereas numbers and percentages were categorical variables. Fisher’s exact test was used to compare adverse events. Results: The study cohort consisted of 59 men in the 7F sheath group and 50 men in the 6F sheath group. Radial artery spasm and catheter kink were significantly lower in the 7F group compared to the 6F sheath group. The overall number of adverse events, including asymptomatic radial artery occlusion, was notably lower in the 7F group. Conclusions: The method of using the mother-and-child technique compared with a 6F group decreased overall adverse events, indicating improved safety for TRA.